Longitudinal changes in psychological distress in a cohort of people who inject drugs in Melbourne, Australia. (1st November 2016) - Scott, Nick; Carrotte, Elise R.; Higgs, Peter; Cogger, Shelley; Stoové, Mark A.; Aitken, Campbell K.; Dietze, Paul M.
Highlights: Psychological distress was examined in a cohort of people who inject drugs (PWID). We found higher levels of psychological distress in PWID than the general population. Average levels were consistent over time, masking within-individual change. Assault and intentional overdose predicted increases in psychological distress. Temporal factors may drive higher levels of distress reported by women. Abstract: Background: Previous research into psychological distress among people who inject drugs (PWID) is predominantly cross-sectional; we determined longitudinal predictors of change in psychological distress among a cohort of PWID. Method: We examined Kessler Psychological Distress Scale (K10) scores from 564 PWID (66% male) enrolled in the Melbourne Injecting Drug User Cohort Study. Gender-stratified linear models with fixed effects for each participant were used to examine correlates of change in individual K10 scores. Further linear regressions of adjusted K10 scores were used to measure correlations between demographic variables. Results: Participants reported higher K10 scores (higher psychological distress) than the general Australian population (mean K10 scores 23.4 (95%CI 22.6–24.2) and 14.5 (95%CI 14.3–14.7) respectively). The cohort's mean K10 score did not significantly differ over time, but individual variations were common. Women reported higher K10 scores than men (mean baseline K10 scores 25.2 (95%CI 23.9–26.6) and 22.4 (95%CI 21.5–23.3) respectively), however no significant differences remained after controlling for temporal factors. Key predictors of increases in K10 scores were being the victim of an assault in the past six months ( P  < 0.001 for women and men) and intentionally overdosing in the past 12 months ( P =  .010 for women and P  < 0.001 for men). Conclusions: PWID experience higher levels of psychological distress than the general population. Temporal rather than individual factors may account for the higher levels of psychological distress reported among women. Interventions to reduce rates of assault and/or intentional overdose should be explored to reduce high levels of psychological distress among PWID.